Long-term fiscal projections and their relationship with the intertemporal budget constraint: An application to New Zealand - John Janssen (New Zealand Government, The Treasury, 2002)
The fiscal gap calculates the change in fiscal policy settings needed to achieve a particular debt target at some point in the future. This working paper calculates fiscal gaps for New Zealand under a range of scenarios, including alternative spending growth, debt targets and interest rates. A positive (negative) fiscal gap indicates that a permanent increase (decrease) in the primary surplus is required to achieve a selected debt target in a particular terminal year. The scenarios suggest that under a range of alternative assumptions the fiscal gap out to 2051 is positive. These results are in accord with previous long-term fiscal projections, which, unlike the fiscal gap, have not been explicit about the nature of long-term fiscal imbalances. The analysis provides a platform for the further examination of potential long-term fiscal imbalances under a wider range of assumptions (e.g., around demographics, labour force participation, health spending) as well as alternative modelling techniques that allow for uncertainty.
Keywords: E62; H60; 330; Long-term fiscal imbalance; intertemporal budget constraint